STUDI TENTANG PRODUCT ADVANTAGE, SERVICE QUALITY DAN BANK LOCATION TERHADAP SAVING DECISION PADA BANK SYARIAH (Studi Pada Nasabah Bank Syariah Mandiri & Bank Muamalat di Kota Semarang ) - Adi, Rifqi Nugroho; Ferdinand, Augusty Tae; Soesanto, Harry (Master of Management Diponegoro University, 2016)
The purposes of this research are to analyze the influence of product advantage, bank location and service quality to increase saving decision at sharia banking. The research’s object which do in this cases are the customers of Bank Muamalat and Bank Syariah Mandiri in the Semarang city. There are 150 respondents and this research used purposive sampling technic.The data analyze technic which used in this case is the structural equation model (SEM) by AMOS 22 software. The result using SEM showed that criteria goodness of fit full model ischi-square= 221,661, probability = 0,000, CMIN/DF = 1,539, GFI = 0,870, AGFI = 0,828, TLI = 0,864, CFI = 0,886, and RMSEA = 0,60. The results said that the models in this research can be used.The results showed that the product innovation does not have effect on product advantage, product advantage has a positive and significant effect on saving decision, bank location does not have effect on saving decision, salespeople competence has a positive and significant effect on service quality, and service quality has a positive and significant effect on saving decision. According to this research, there are a few limitation on this research and upcoming research’s agenda that can be done in the next research.